2020
DOI: 10.12998/wjcc.v8.i24.6213
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut microbiome in regulating the effectiveness of metformin in reducing colorectal cancer in type 2 diabetes

Abstract: The prevalence of colorectal cancer (CRC) and type 2 diabetes mellitus (T2DM) is increasing globally. It is rarely noticed that the incidence of CRC is higher in patients with T2DM. What needs to be mentioned is that metformin, a commonly used clinical drug for T2DM, attracts scholars’ attention because of its benefits in lowering the risk of developing CRC. Hence, we try to find the common grounds of initiation of T2DM and CRC and the reason why metformin reduces the risk of CRC in patients with T2DM. We noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…136, 137 Metformin interacts with F. nucleatum by reducing its levels and antagonizing the progression of CRC. 138 Beyond reducing the levels of this strain, metformin is associated with the inhibition of the TLR4/MYD88/NF-ΚB pathway, 139 thus reducing the inflammation and metastasis in CRC (Fig. 1).…”
Section: Metformin and Colorectal Cancer (Crc)mentioning
confidence: 99%
“…136, 137 Metformin interacts with F. nucleatum by reducing its levels and antagonizing the progression of CRC. 138 Beyond reducing the levels of this strain, metformin is associated with the inhibition of the TLR4/MYD88/NF-ΚB pathway, 139 thus reducing the inflammation and metastasis in CRC (Fig. 1).…”
Section: Metformin and Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Metformin inhibits CRC in T2D patients by altering the abundance of gut microbiota or involving gut microbiota. 113 Metformin can also inhibit microglial activation and neuroinflammation in the brain by regulating intestinal flora in obese mice and thus may be considered a promising candidate for the intervention of cognitive decline related to an obesity-induced imbalance of the gut microbiota. 114 However, due to the complex composition of microbial communities, considerable differences in species, individuals and experimental design, the changes in gut microbes caused by metformin are not consistent, which presents great obstacles for us to better understand the relationship between metformin and gut microbes.…”
Section: Anti-aging Interventions and Intestinal Microbesmentioning
confidence: 99%
“…Anti-diabetic drug such as metformin produced significant changes in the gut microbiome of CRC patients with type 2 diabetes mellitus (T2DM). Comparative analysis among CRC patients with T2DM showed that metformin was associated with increase in Firmicutes and decrease in Bacteroidetes and Fusobacteria at the phyla level, while Bifidobacterium increased at genus level, whereas the abundance of pro-tumorigenic species F. nucleatum was decreased ( 30 ). Metformin treatment in T2DM has shown to increase the gut bacteria associated with enhanced production of SCFA such as butyrate and propionate which improve glucose metabolism and homeostasis ( 31 ).…”
Section: Gut Microbiome and Colorectal Cancermentioning
confidence: 99%
“…Anti-diabetic drugs such as metformin induces changes in the gut microbiome of T2DM patients developing CRC. Comparative analysis showed that initiation of metformin in T2DM patients with CRC was associated with an increase in Firmicutes and decrease in Bacteroidetes and Fusobacteria at the phyla level while at genus level increase in Bifidobacterium with an associated decrease in F. nucleatum ( 30 ). Metformin treatment of T2DM has shown to enhance the microbial richness of the colon associated with enhanced production of SCFAs such as butyrate and propionate which potentially improves glucose metabolism and homeostasis ( 31 ).…”
Section: Gut Microbiome and Colorectal Cancermentioning
confidence: 99%